أثر برنامج تدريبي باستعمال برامج الكمبيوتر قبل و بعد المباراة على التفكير و الأداء التكتيكي الهجومي للاعبي كرة القدم دراسة ميدانية بفريقي أواسط أهلي برج بوعريريج و شباب العلمة موسم 2015 – 2016 - فريد كربيع (My University, 2018)
The present work consists of evaluating the effect of a training program by using modern computer software on the development of offensive tactical thinking and the individual and collective performance of football players. The researcher used the experimental method by planning two groups: an experimental group and a control group. The sample we worked on consisted of 15 players from the CABBA team - experimental - and 15 players from MC Eulma - control - U 19 years old. An offensive tactical thinking test was used, which contains 26 positions and situation. the training program has reached 15 weeks, this program consists of theoretically exposing the training exercises and the tactical situations-before the practical sessions-by using static drawings followed by the explanation of the objective of each exercise and the role of each player. The researcher chose two software packages: Tactics Manager and Dartfish, he found: - There are statistically significant differences between the first test and post-test for experimental group members in tactical offensive thinking in favor of post-test. - There are statistically significant differences in post-test degrees between the two groups of the experiment and the control in favor of the experimental group. The researcher concluded that the training program by using a computer software packages has a positive impact on thinking and offensive tactical performance in football .
Keywords: Computer Software - Tactical Thinking – Football- Tactical Performance